Model-view-controller architecture cafeteria management system with food pre-ordering - Ewe, Chun Kit (2021)
This is a cafeteria management system with food pre-ordering for academic purpose. It is developed to reform the traditional business model in school cafeteria and bring a new trend to them. As during this Covid-19 pandemic, the students are not allowed to get meal directly from the canteen. The traditional canteen’s business model requires a lot of manual work from the staffs. Especially during this covid-19 pandemic, the staffs need to deal with the pre-order records which generated by using excel. The flow of ordering would cause human errors, for instances users break the rules when placing order, incorrect data migration, and others. All these human errors will cause the users and hawkers receive the incorrect results and affect their purchasing experience. Therefore, this system is going to provide the school cafeteria to have a better management. Due to the unclear user requirement, throwaway prototyping is conducted as the methodology. This methodology is mostly used when the user requirements are not clear is because it allows the developer to send the prototype and do further enhancement to fulfil the user requirements. MVC will be taken as the architectural pattern of this project to reduce the redundancy of code. This project will study and compare the similar systems and interview a secondary school’s food pre-ordering system as references.